A major practicum at Kraft Foods Philippines, Inc., Sucat Road, Paranaque City, Metro Manila - Molina, Ninalyn Fe Deparroco (2007)
The trainee conducted her plant practice at Kraft Foods Philippines, Inc., located at 8378 Dr. A. Santos Ave. Sucat road, Paranaque City, Metro Manila. She accomplished her 288 hours requirement within 29 days from April 17, 2006 to May 29, 2006. The trainee was assigned to Sensory Room where she gained knowledge and techniques on ways of checking whether products such as processed cheese spreads, processed cheese loaves and blocks, and spoonables conform to the set standards through visual inspection and analytical measurements. Along the training duration, the trainee encountered minor problems and in this paper, made some recommendation to address these concerns
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2007
Keywords: Kraft Foods Philippines; Cheese products; Cheese products -- Processes